Semiconductive‐Ferroelectric‐Enhanced Photo‐Electrochemistry with Collective Improvements on Light Absorption, Charge Separation, and Carrier Transportation. Issue 21 (11th October 2021) - Gong, Yuedong; Li, Yi; Chen, Jianguo; Guo, Hui; Sun, Chenwei; Li, Chun; Cao, Ruiguo; Jiao, Shuhong; Huang, Lu; Yang, Weiguang; Yu, Yanhao
Abstract: The efficiency of photo‐electrochemistry is jointly determined by multiple factors such as light absorption, charge separation, and carrier transportation. It is essential to maximize all of them but has proved challenging especially for photoelectrodes made from wide‐bandgap semiconductors. Here, a conceptually new strategy noted as semiconductive‐ferroelectric‐enhanced photo‐electrochemistry (SF‐PEC) is reported based on a doped TiO2 ‐Ba x Sr1− x TiO3 (BST) core–shell nanowire array. Through an in situ surface conversion and an electron/nitrogen codoping process, a self‐polarized, surface‐amorphized, and doped BST thin layer is created on the surface of TiO2, resulting in a semiconductive‐ferroelectric‐enhanced TiO2 (SF‐TiO2 ) photoelectrode. Compared with pristine TiO2 and ferroelectric‐enhanced TiO2 (F‐TiO2 ), the SF‐TiO2 has stronger light absorption, greater charge separation, and faster carrier transportation, which is identified to be a synergistic outcome of the reduced bandgap, moderate ferroelectric polarization, and high carrier density and mobility. The photocurrent density of SF‐TiO2 reaches 1.87 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE), 1.39 and 2.46 times higher than that of F‐TiO2 and TiO2, respectively. The SF‐TiO2 maintains over 90% of its photocurrent density after being aged in air for 11 months. This work provides new insights to extend the efficiency limit of photo‐electrochemistry. Abstract : Semiconductive ferroelectric is introduced to improve the efficiency of photo‐electrochemistry. Through creating a doped, self‐polarized, and surface amorphized barium strontium titanate thin surface coating, the TiO2 ‐based photoelectrode achieves a collective improvement on light absorption, charge separation, and carrier transportation, ultimately leading to an outstanding photocurrent density and photo‐electrochemistry efficiency, while maintaining a good operational stability.